2014
DOI: 10.1101/gr.164707.113
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent epimutations activate gene body promoters in primary glioblastoma

Abstract: Aberrant DNA hypomethylation may play an important role in the growth rate of glioblastoma (GBM), but the functional impact on transcription remains poorly understood. We assayed the GBM methylome with MeDIP-seq and MREseq, adjusting for copy number differences, in a small set of non-glioma CpG island methylator phenotype (non-G-CIMP) primary tumors. Recurrent hypomethylated loci were enriched within a region of chromosome 5p15 that is specified as a cancer amplicon and also encompasses TERT, encoding telomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 77 publications
(95 reference statements)
3
40
0
Order By: Relevance
“…The gene encoding HIGD1A is located on human chromosome 3p22.1, where many tumor suppressor genes reside, and these are often inactivated via epigenetic mechanisms (Bhat Singh and Amare Kadam, 2013; Buchhagen et al, 1994). From genome-wide analyses of aberrant DNA methylation in glioblastoma multiforme (GBM) (Nagarajan et al, 2014), we identified two candidate regions near the Higd1a promoter that exhibited GBM-specific hypermethylation. As indicated in figure 3B, one of these regions, located upstream of the 5′ CpG island promoter, in a CpG island “shore,” contains consensus core hypoxia response elements (HRE) (blue underlined).…”
Section: Resultsmentioning
confidence: 99%
“…The gene encoding HIGD1A is located on human chromosome 3p22.1, where many tumor suppressor genes reside, and these are often inactivated via epigenetic mechanisms (Bhat Singh and Amare Kadam, 2013; Buchhagen et al, 1994). From genome-wide analyses of aberrant DNA methylation in glioblastoma multiforme (GBM) (Nagarajan et al, 2014), we identified two candidate regions near the Higd1a promoter that exhibited GBM-specific hypermethylation. As indicated in figure 3B, one of these regions, located upstream of the 5′ CpG island promoter, in a CpG island “shore,” contains consensus core hypoxia response elements (HRE) (blue underlined).…”
Section: Resultsmentioning
confidence: 99%
“…S10). Nucleosome positioning analysis from micrococcal nuclease-digested H3K4me3 ChIP-seq(24) data revealed that both mutation positions lie within a nucleosome free region, with the upstream nucleosomes containing the H3K4me3 modifications (fig. S10).…”
mentioning
confidence: 99%
“…In a previous study, Nagarajan et al found a genomic region, just upstream of the first exon on an alternative TERT transcript, that was hypomethylated in three of five glioblastoma tumors. They also described elevated expression of an alternative TERT transcript in glioblastoma samples compared to normal brain [38]. …”
Section: Discussionmentioning
confidence: 99%